Dissolution enhancement of chlorzoxazone using cogrinding technique - Raval, Mihir K.; Patel, Jaydeep M.; Parikh, Rajesh K.; Sheth, Navin R. (International Journal of Pharmaceutical Investigation)
Purpose: The aim of the present work was to improve rate of dissolution and processing parameters of BCS class II drug, chlorzoxazone using cogrinding technique in the presence of different excipients as a carrier. Materials and Methods: The drug was coground with various carriers like polyethylene glycol (PEG 4000), hydroxypropyl methylcellulose (HPMC) E50LV, polyvinylpyrrolidone (PVP)K30, Kaolin and Neusilin US2 using ball mill, where only PEG 4000 improved dissolution rate of drug by bringing amorphization in 1:3 ratio. The coground mixture after 3 and 6 h was evaluated for various analytical, physicochemical and mechanical parameters. Results: The analysis showed conversion of Chlorzoxazone from its crystalline to amorphization form upon grinding with PEG 4000. Coground mixture as well as its directly compressed tablet showed 2.5-fold increment in the dissolution rate compared with pure drug. Directly compressible tablets prepared from pure drug required a large quantity of microcrystalline cellulose (MCC) during compression. The coground mixture and formulation was found stable in nature even after storage (40°C/75% relative humidity). Conclusions: Cogrinding can be successfully utilized to improve the rate of dissolution of poorly water soluble drugs and hence bioavailability.
Keywords: Amorphization; chlorzoxazone; cogrinding; dissolution enhancement; heckel analysis